2022
DOI: 10.3390/cancers14071793
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Treatment Comparison of Larotrectinib versus Entrectinib in Treating Patients with TRK Gene Fusion Cancers

Abstract: Information regarding the comparative efficacy of first-generation receptor tyrosine kinase inhibitors is limited. This matching-adjusted indirect comparison (MAIC) evaluated differences in efficacy and safety across larotrectinib and entrectinib trials. Data from clinical trials for larotrectinib (LOXO-TRK-14001 (NCT02122913), SCOUT (NCT02637687), and NAVIGATE (NCT02576431)) and entrectinib (ALKA-372-001 (EudraCT 2012-000148-88), STARTRK-1 (NCT02097810), and STARTRK-2 (NCT02568267)) were used. Adults (≥18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Garcia-Foncillas et al ( 2022) reported that the MAIC demonstrated no statistically significant differences between larotrectinib and entrectinib for serious TRAEs or TRAEs leading to discontinuation. 86 As previously noted, firm conclusions should not be drawn from this MAIC regarding the comparative safety of entrectinib and larotrectinib due to important limitations with the analysis.…”
Section: Harmsmentioning
confidence: 89%
See 2 more Smart Citations
“…Garcia-Foncillas et al ( 2022) reported that the MAIC demonstrated no statistically significant differences between larotrectinib and entrectinib for serious TRAEs or TRAEs leading to discontinuation. 86 As previously noted, firm conclusions should not be drawn from this MAIC regarding the comparative safety of entrectinib and larotrectinib due to important limitations with the analysis.…”
Section: Harmsmentioning
confidence: 89%
“…In the absence of direct or indirect evidence comparing entrectinib and larotrectinib in the submission, CADTH conducted a literature search to identify any relevant published indirect comparisons, and identified 1 MAIC that compared entrectinib and larotrectinib in adult patients with NTRK gene fusion-positive tumours. 86 Garcia-Foncillas et al ( 2022) reported that, compared with entrectinib, larotrectinib was associated with a statistically significantly greater duration of OS and DOR, with statistically significant differences for PFS or ORR. 86 However, due to major limitations associated with this study, firm conclusions for the efficacy and safety end points comparing entrectinib and larotrectinib are not recommended.…”
Section: Comparative Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Two NTRK inhibitors, entrectinib and larotrectinib, received an agnostic approval from the FDA based on the results of the studies, which included a wide spectrum of NTRK-rearranged tumors [48,49]. Indirect comparisons of clinical data suggest that larotrectinib may be more efficacious than entrectinib in NTRK-driven malignancies [50][51][52]. Although NTRK1-3 rearrangements are frequently presented as an example of agnostic medicine, their actual utility is limited by some factors.…”
Section: Ntrk1-3 Rearrangementsmentioning
confidence: 99%
“…Clinical trials showed the significant advantage of larotrectinib administration in patients with TRK fusion-positive primary central nervous system (CNS) tumors. It demonstrated rapid and durable responses, a high disease control rate and a favorable safety profile [46,47].…”
Section: Larotrectinibmentioning
confidence: 99%